Novel Method for Fire Retardancy of Cotton Fabrics Coated by Spinach Leaf Extract Assisted by Corona Discharge Plasma - Valentinus Galih Vidia Putra; Andrian Wijayono; Juliany Ningsih Mohamad (Balai Besar Kerajinan dan Batik, 2020)
The application of material physics in the functional textile field has been widely applied, one of which is plasma technology. In this research, the fire-retardant properties have been developed in the cotton fabric textile material using spinach leaf extract and comparison of fire-retardant resin on the market using plasma technology. The flame-retardant is applied to the cotton fabric using the atmospheric-pressure plasma method with a tip-cylinder electrode. The cotton fabric used is a cotton fabric that has undergone a process of bleaching and mercerization. In this research, two types of methods have been carried out, namely the immersion method on the fire-retardant resin substance with atmospheric pressure plasma pre-treatment and the immersion method on spinach leaf extract with atmospheric pressure plasma treatment. Research shows that there is an increase in the fire-retardant properties of cotton fabrics that have been given treatment. The assessment of fire-retardant properties was tested using the standard method of fire-retardant ASTM D6413-08 vertical method. In this research, atmospheric-pressure plasma treatment with a time variation of 2 minutes and 4 minutes has been carried out. The results showed that the cotton fabric treated with the immersion method on spinach leaf extract and atmospheric pressure plasma pre-treatment had better fire-retardant properties. It has also been found that the length of time the plasma treatment will affect the fire-retardant properties of cotton fabrics.